Montelukast Improves Symptoms and Lung Function in Asthmatic Women Compared With Men - Renata Esposito; Giuseppe Spaziano; Domenico Giannattasio; Francesco Ferrigno; Angela Liparulo; Antonietta Rossi; Fiorentina Roviezzo; Maurizio Sessa; Maurizio Sessa; Maddalena Falciani; Liberato Berrino; Mario Polverino; et al. (Frontiers Media S.A., 2019)
Purpose: Gender differences exist in the prevalence of asthma and allergic diseases, partially due to the effects of sex hormones on the development of allergic manifestations. Women, compared with men, are more prone to suffer allergic asthma, experience difficulties in controlling asthma symptoms, and show adverse responses to drugs. However, there are knowledge gaps on the effectiveness of anti-leukotrienes drugs on lung function, symptoms, and pulmonary and systemic inflammation in adult asthmatic women compared with men. We conducted a prospective cohort study to characterize the effectiveness of an anti-leukotrienes drug, montelukast (MS), in asthmatic adult women and men.Methods: Twenty-one asthmatic subjects (11 women and 10 men), who were on low-dose inhaled corticosteroids (ICS), were treated with MS. The optimal control of the symptoms was achieved in both groups according to the Global Initiative for Asthma guidelines. At enrollment, and after 13 weeks from the beginning of MS, pulmonary function tests and asthma control tests were performed, and the fraction of exhaled nitric oxide and blood eosinophils levels were measured.Results: From baseline until the end of the study, women treated with MS + ICS had better control of the asthmatic symptoms, defined as higher asthma control test (ACT) score (17.00 ± 1.07 to 23.36 ± 0.45; p < 0.0015), improved pulmonary function [with higher forced expiratory volume in 1 s (from 77.25 ± 6.79 to 103.88 ± 6.24; p < 0.0077)], and forced vital capacity (from 91.95 ± 6.81 to 113.17 ± 4.79; p < 0.0183) compared with men. Interestingly, MS + ICS-treated women had significantly lower levels of blood eosinophils (from 5.27 ± 0.30 to 3.30 ± 0.31; p < 0.0449) and exhaled nitric oxide (from 44.70 ± 7.30 to 25.20 ± 3.90; p < 0.0294) compared with men.Conclusion: The treatment with MS, added to ICS, in women leads to better control of symptoms, better management of lung function, and decreased inflammation levels compared with ICS + MS treatment in men.